2009
DOI: 10.1016/j.ejcts.2009.04.069
|View full text |Cite
|
Sign up to set email alerts
|

Results of combined modality treatment in patients with non-small-cell lung cancer of the superior sulcus and the rationale for surgical resection

Abstract: This schedule of induction therapy with high-dose radiation and concurrent cisplatinum was safe and highly effective in fit patients. At this time, pathologic complete response cannot be reliably recognised preoperatively, and better tools for response assessment are critical for more tailored treatment of patients with SST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
3
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 26 publications
1
29
3
1
Order By: Relevance
“…Even long-term (5-year) survival rates resulted improved reaching 44% (SWOG 9416) and 56% (JCO 9806), respectively. Based on these data, the modern standard treatment for sulcus superior tumors has become the combination of induction CT/RT followed by radical surgical resection (25,29,(35)(36)(37)(38)(39)(40)(41)(42)(43) (Table 1).…”
Section: A B Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Even long-term (5-year) survival rates resulted improved reaching 44% (SWOG 9416) and 56% (JCO 9806), respectively. Based on these data, the modern standard treatment for sulcus superior tumors has become the combination of induction CT/RT followed by radical surgical resection (25,29,(35)(36)(37)(38)(39)(40)(41)(42)(43) (Table 1).…”
Section: A B Cmentioning
confidence: 99%
“…Operative mortality rate ranges from 0% to 6.9% and morbidity from 11% to 47% (25,29,(35)(36)(37)(38)(39)(40)(41)(42)(43). In particular, the SWOG 9416 (35) and JCO 9806 (36) phase II trials showed operative mortality rates of 2.3% and 3% and morbidity rates of 52% and 14%, respectively.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wyniki badań bez losowego doboru chorych wskazują, że zastosowanie przedoperacyjnej chemioterapii w skojarzeniu z napromienianiem jest uzasadnione w przypadku lokalizacji nowotworu w szczycie płuca (guz Pancoasta) [39][40][41]. We wcześniejszych badaniach w przedoperacyjnej radiochemioterapii stosowano dawki w granicach 45-50 Gy, ale nowsze doniesienia wskazują, że bezpiecznie można zastosować wyższą dawkę [40].…”
Section: Przedoperacyjna Chemioterapiaunclassified
“…En-bloc resection of the upper lobe, ribs, nerves (brachial plexus) plus or minus vessels is recommended. Many studies published in the past 10 years have established the gold standard in the field as induction therapy consisting of high dose radiotherapy with concurrent cisplatin-based chemotherapy, followed by surgery 4-6 weeks later [124][125][126][127][128][129]. Using this multimodality scheme, perioperative mortality is low and 5-year survival rates are now consistently .40%.…”
Section: Superior Sulcus Tumours (Pancoast Tumours)mentioning
confidence: 99%